Understanding the Role of Brand Attachment in the Automotive Luxury Brand Segment - Milheiro, Abílio (2024)
The automotive trade is one of the main drivers of world economies, contributing to the sustainability and competitiveness of countries at a global level. The luxury sub-segment is the one facing the most significant growth and the one which presents the greatest challenges in the business-to-consumer (B2C) relationship. Brand Attachment refers to the cognitive and effective connection between consumers and “their” brands. The central objective of this research is to analyze, measure, and understand the impact of Brand Attachment on consumer behavior, in the specific context of the luxury segment of the automotive market. The conceptual model that is proposed seeks to highlight and study the possible connections and associations between Brand Attachment, satisfaction, commitment, trust, expectations, and loyalty with the brand selected for this study, the luxury automotive brand Porsche. The selected methodology was based on a case study based in the Portuguese market and the application of a questionnaire to customers of Porsche from Portugal. The results obtained through the empirical data allowed us to reach the conclusion that respondents who have a stronger affective and emotional connection with Porsche (intense level of Brand Attachment) tend to be those who are more satisfied and confident with the brand and are, consequently, more loyal. This study represents an important contribution to research on Brand Attachment in marketing and strategic management in the automotive sector, particularly in the Portuguese market, and supports the definition of the best marketing strategies to promote fruitful B2C relationships